EVALUASI PASCA-DIKLAT JURU UKUR TAMBANG TERHADAP PERUBAHAN PERILAKU ALUMNI PT TIMAH TBK. - Revi Timora Salajar (PPSDM Geominerba, 2021)
The need for large number of mine surveyors at PT Timah Tbk. is very much needed until now. This is an embodiment of fulfilling the mandate in the Minister of Energy and Mineral Resources Regulation No. 26 of 2018 concerning the Implementation of Good Mining Engineering Rules, Article 7, “every mining business licence must have the competent mining technical personnel in accordance with the provisions of laws and regulations”. As a result of these regulations, PT Timah Tbk. seeks to include its employees in the Training and Certification of the mine surveyor at PPSDM Geominerba. This post-training evaluation method is carried out by using a questionnaire to the alumni of mine surveyor training and certification of PT Timah Tbk. The result of the post-training evaluation specifically found that the Training and Certification of the mine surveyor was considered to be useful and support the work so that the theory obtained can be applied better.